The Relationship between Formula Milk Supplementation and the Nutritional Status of Low Birth Weight Infants at the Age of 0-6 Months at the Makassar City Health Center in 2020-2022 - Syahrir, Syamsuriani - (E-Jurnal Medika Udayana; Vol 13 No 10 (2024): E-Jurnal Medika Udayana, 2024)
Low birth weight (LBW) are babies born weighing less than 2,500 grams or also known as low birth weight infants (LBWI). There are several problems that can be caused to babies with low birth weight (<2,500 grams), namely hypothermia, digestive disorders, lung development disorders, immunological disorders, immature liver, immature kidneys, and hypoglycemia. The maturity of the function of the digestive tract in babies born with normal weight is certainly different from babies born with low birth weight, so that the provision of nutrition to babies born with normal weight will also be different from the provision of nutrition to LBW babies. The purpose of this study was to determine the relationship between giving formula milk supplementation and the nutritional status of babies with a history of LBW at the age of 0-6 months at the Makassar City Health Center in 2020-2022. This type of research is quantitative analytic research with the research approach used is cross sectional. The sampling method is a purposive sampling technique of 160 samples. The research results show chi square found the p-value is 0.001 (p<0.05) on BB/U and PB/U, on BB/PB, with a value chi square got 0.080. The conclusion in this study is that there is a relationship between giving formula milk supplementation and the nutritional status of BB/U and PB/U, but there is no relationship between BB/PB of low birth weight babies at the age of 0-6 months at the Makassar City Health Center in 2020-2022.